Optical properties in 1D photonic crystal structure using Si/C_（60） multilayers - 谌静 唐吉玉 韩培德 陈俊芳 (Journal of semiconductors, 2009)
The feasibility of using Si/C60 multilayer films as one-dimensional （1D） photonic band gap crystals was investigated by theoretical calculations using a transfer matrix method （TMM）. The response has been studied both within and out of the periodic plane of Si/C60 multilayers. It is found that Si/C60 multilayer films show incomplete photonic band gap （PBG） behavior in the visible frequency range. The fabricated Si/C60 multilayers with two pairs of 70 nm C60 and 30 nm Si layers exhibit a PBG at central wavelength of about 600 nm, and the highest re？ectivity can reach 99%. As a consequence, this photonic crystal may be important for fabricating a photonic crystal with an incomplete band gap in the visible frequency range.